Study of fault repair control mode for distribution network based on automation and information under big-maintenance system - Lacheng Pang; Jing Zhou; Xinhe Chen; Weihua Ye; Wenbin Zhang (22nd International Conference and Exhibition on Electricity Distribution (CIRED 2013), 2013)
The subject addressed is organizational structure mode and control process mode of distribution network rush-repair. Repair control process based on information support platform is built, and the interactive method of various information systems is proposed, providing theoretical and practical references for further improvement of fault rush-repair control in future smart distribution system. (4 pages)